Silicon-based polymers and materials - Chruściel, Jerzy J. (De Gruyter, 2022)
"Silicon based materials and polymers are made of silicon containing polymers, mainly macromolecular siloxanes (silicones). This book covers the different kinds of siliconbased polymers: silicones, silsesquioxanes (POSS), and silicon-based copolymers. Other silicon containig polymers: polycarbosilanes, polysilazanes, siloxane-organic copolymers, silicon derived high-tech ceramics: silicon carbide and oxycarbide, silicon nitride, etc. have also a very important practical meaning and a hudge number of practical applications. These materials make up products in a variety of industries and products, including technical and medical applicatons. Polycrystalline silicon is the basic material for large scale photovoltaic (PV) applications as solar cells. Technical applications of crystalline (c-Si) and amorphous (a-Si) silicon (fully inorganic materials), silicon nanowires are still quickly growing, especially in the fi eld of microelectronics, optoelectronics, photonics. and photovoltaics, catalysts, and different electronic devices (e.g. sensors, thermoelectric devices). This book is ideal for researchers and as such covers the industrial perspective of using each class of silicon based materials."--Publisher.